KEANEKARAGAMAN DAN KELIMPAHAN ECHINODERMATA DI PANTAI PANCURAN PULAU LEMBEH - Yudith A. Christianti; Farnis B. Boneka; Erly Y. Kaligis; Chatrien A.L. Sinjal; Billy Th. Wagey; Ridwan Lasabuda (JURNAL PESISIR DAN LAUT TROPIS, 2023)
Echinodermata are found quite commonly in the tidal areas of Lembeh Island but their diversityand abundance have not been well documented. The purpose of this study was to determine the typesof Echinoderms and their abundance at Pancuran Beach, Lembeh Island, Bitung City. Samples weretaken at two stations using the Lincoln-Smith Transect method 2 x 50 m which was stretchedperpendicular to the beach with three replications. Samples were identified in situ and the number ofindividuals of each species was noted. The results showed that in Pancuran Beach there were 18species of phylum Echinodermata; with details of 7 species from the Asteroidea class, 5 species ofEchinoidea, 4 species of Ophiuroidea, 2 species of Holothuroidea. The results of the analysis using thediversity index show that the diversity of Echinodermata at both stations is in the medium category,characterized by the value of H' = 2.06 for station I and H'= 2.35 for station II. At station 1, the type ofOphiocoma erinaceus has the highest density of 15 ind/100m2 and a relative abundance of 23.68%. Atstation II Echinothrix diadema has the highest abundance of 12 ind/100m2 with a relative abundance of17.14%. Common species found in both stations are Diadema setosum, Echinometra mathaei,Echinothrix diadema, Holothuria atra, Ophiocoma erinaceus, and Ophiocoma scolopendrina.Keywords: Lembeh Island, Diversity, Abundance, Echinoderms ABSTRAKEchinodermata ditemukan cukup umum di daerah pasang surut Pulau Lembeh namunkeanekaragaman dan kelimpahannya belum sepenuhnya didokumentasikan dengan baik. Tujuanpenelitian ini adalah untuk mengetahui jenis-jenis Echinodermata dan kelimpahannya di PantaiPancuran, Pulau Lembeh Kota Bitung. Sampel diambil pada dua stasiun dengan menggunakan metodeLincoln-Smith Transect 2 x 50 m yang dibentangkan tegak lurus ke arah pantai dengan tiga replikasi.Sampel diidentifikasi secara insitu dan jumlah individu tiap spesies dicatat. Hasil menunjukkan bahwadi Pantai Pancuran terdapat 18 spesies filum Echinodermata; dengan rincian 7 spesies dari kelasAsteroidea, 5 spesies Echinoidea, 4 spesies Ophiuroidea, 2 spesies Holothuroidea. Hasil analisamenggunakan indeks keanekaragaman menunjukkan bahwa diversitas Echinodermata pada keduastasiun dalam kategori sedang, ditandai dengan nilai H' = 2,06 untuk stasiun I dan H'= 2,35 untukstasiun II. Pada stasiun 1, jenis Ophiocoma erinaceus paling tinggi densitasnya yakni 15 ind/100m2dan kelimpahan relatif 23,68%, Pada stasiun II Echinothrix diadema memiliki kelimpahan tertinggi yakni12 ind/100m2 dengan kelimpahan relatif 17,14%. Jenis yang umum terdapat pada kedua stasiun adalahDiadema setosum, Echinometra mathaei, Echinothrix diadema, Holothuria atra, Ophiocoma erinaceus,dan Ophiocoma scolopendrina. Kata kunci: Pulau Lembeh, Keanekaragaman, Kelimpahan, Echinodermata